Principles of social psychology - Stangor, Charles; Jhangiani, Rajiv; Tarry, Hammond; BC Open Textbook Project; BCcampus (BCcampus Open Textbook Project, 2014)
"The first International edition of this textbook provides students with an introduction to the basic concepts and principles of social psychology from an interactionist perspective. The presentation of classic studies and theories are balanced with insights from cutting-edge, contemporary research. An emphasis on real world examples and applications is intended to guide students to critically analyze their situations and social interactions in order to put their knowledge to effective use."--BCcampus website.
This work is licensed under the Creative Commons Attribution-NonCommercial-ShareAlike License.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Description based on version viewed on BCcampus OpenEd website; title from pdf title page.
Keywords: Social psychology -- Textbooks; Electronic books